PENEGAKAN HUKUM DI INDONESIA: APAKAH INDONESIA NEGARA HUKUM? - Siti Merida Hutagalung (Sociae Polites, 2011)
AbstractLaw problems are not finished yet until Indonesia entering its reformation era. AlthoughIndonesia actually is the Constitutional State, constitution has failed to provide protectionto the people. Supremacy of Law which is mandated by the Constitution 1945 is failed to beconducted, while law apparatus like public prosecutors, judges, polices and lawyers areinvolved playing the law. And then term as Law Mafia becomes familiar for public. Thegovernment has initiated various efforts to solve the law problems by making the NationalLaw Commission, Corruption Eradication Commission, Judicial Commission, Special TaskForce for Law Mafia, etc but it seems that itâ€™s need a long time to improve the lawenforcement in Indonesia. But, law enforcement is still far from the ideals of rechts idÃ©e,and the aim of the State Law (Homeland/NKRI) as contained in the preamble of theConstitution paragraph four: developing the intellectual life of the Indonesian nation;creating more prosperous life or public welfare, and the fourth principle of Pancasila that isrealizing social justice for all the people of Indonesia.Keywords: Rule of law, Law enforcement, Constitution 1945, Law institution